The effect of small games in learning geometric shapes, mathematical numbers, and developing some motor skills among kindergarten children - et. al., Aujeed madlool Abbas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Childhood is considered one of the most important life stages that a person goes through from birth to adulthood, as it is the main pillar for the proper and integrated construction of the child at all skill levels, physical, mental, cognitive, psychological and emotional, as it affects his behavior and personality in all its dimensions, but the interest in developing physical and motor capabilities of Children have become one of the things that modern science pays attention to through the close relationship between them and human development. Therefore, this concern requires an integrated preparation from early childhood until reaching the highest levels and in all mental, psychological, skill, emotional and physical aspects. Thus, the importance of research lies in the use of small games in order to develop basic motor skills and mental and mental capabilities for children aged (5-6) years, where the child can perform movements according to his potential and abilities through freedom of movement and far from the matter in motor performance, which will contribute in the future to increase Develop those capabilities.The study aimed to identify the effect of using small games on developing basic skills and acquiring some mathematical concepts for kindergarten children (5-6). The study sample consisted of (40) children divided into two equal control and experimental groups, they were chosen randomly, where the experimental group underwent a training program for a period of (18) weeks with two training units per week for a period of (45) minutes per unit, and the researchers used the experimental approach by the method of measurement Pre and post for two experimental and control groups due to its suitability for the nature of the study. Pre and post measurements were performed using specially designed tests.The results showed an improvement and a positive effect of the training program in small games on developing basic skills and acquiring some mathematical concepts through the difference between the pre and post measurements of the sample members. In addition to the presence of statistically significant differences between the experimental and control groups in favor of the experimental group.